2021
DOI: 10.1371/journal.pone.0258588
|View full text |Cite
|
Sign up to set email alerts
|

Items analysis of the Frailty Index (FI-35): Insight in the contribution of each item to the level of frailty

Abstract: Background The FI-35 is a valid multidimensional Chinese frailty assessment instrument. Like other scales, functional measures rely on the information the total score provides. Our research aimed to analyze the contribution of each item. Methods Descriptive statistics were used to summarize the sample characteristics. The expected item score (EIS) was used to determine how the items contribute to the generic measure of frailty. Results This study showed that most of the EIS curves increased across the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…13 A study conducted in China also found that slowness was the most frequent frailty criterion. 16 However, the study conducted by Fried and collaborators 6 found a greater frequency for low physical activity level, followed by slowness, which is in agreement with data described in a study developed in Taiwan. 14 Despite variations in the literature, the results point to issues related to physical aspects, underscoring the need for greater attention to be given to physical activity and body composition in older people.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…13 A study conducted in China also found that slowness was the most frequent frailty criterion. 16 However, the study conducted by Fried and collaborators 6 found a greater frequency for low physical activity level, followed by slowness, which is in agreement with data described in a study developed in Taiwan. 14 Despite variations in the literature, the results point to issues related to physical aspects, underscoring the need for greater attention to be given to physical activity and body composition in older people.…”
Section: Discussionsupporting
confidence: 69%
“…The frequency of frailty criteria varies considerably among studies depending on the characteristics of the population studied, methods employed and cutoff points adopted. [13][14][15][16] The most frequent criteria in the present study were slowness and fatigue. The same criteria were the most frequent in a Brazilian study on cutoff points for frailty status.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations